Profil Penyandang Tunarungu Berprestasi di Cabang Olahraga Atletik Tingkat Nasional - Nesy, Azkia Mardhatillah; Kasiyati, Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2021)
This research was motivated by the discovery of deaf people in the community who had various brilliant achievements and won gold medals at the national level as a contingent for West Sumatra Province in one of the athletic sports, namely running. This study aims to determine what achievements (D) has with a qualitative descriptive study, by knowing the deaf and parents as research subjects. Data collection was carried out through observation, interviews, and documentation study then analyzed to be presented and conclusions drawn. Achievements to the national level at the National Paralympic Week (PEPARNAS) XIV 2012 in Riau by winning a silver medal and the National Paralympic Week (PEPARNAS) XV 2016 in West Java by winning a gold medal. Paralympic Week is held once every four years in Indonesia and is participated by athletes from various provinces. He is active in participating in running competitions at the city, provincial, and national levels. Then (D) will take part in the National Paralympic Week XVI 2021 competition which will be held in Papua.